Dehydration of glucose to 5-hydroxymethylfurfural using zirconium doped mesoporous silica as catalyst - Mérida Morales, Sandra; García-Sancho, Cristina; Ginés-Molina, María José; Cecilia-Buenestado, Juan Antonio; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (My University, 2019)
In recent years, the valorization of carbohydrates coming from lignocellulosic biomass. such as glucose, is gaining attention to obtain high value-added products like 5-hydroxymethylfurfural (HMF). The objective of this work was the dehydration of glucose to HMF by using different mesoporous silica doped with Zr (Zr-KIT-6, Zr-MCM-41, Zr-SBA-15, Zr-SBA-15 (HT) y Zr-HMS) as acid catalysts to maximize the HMF yield, and the study of the influence of textural and acid properties. The mesoporous silicas were synthesized with the same Si/Zr molar ratio= 5. The glucose dehydration was carried out at 150ºC and 175ºC under magnetic stirring. A biphasic reaction system (water:methylisobutylketone (MIBK)) was used in order to avoid side reactions. It was found that the addition of CaCl2 to the aqueous phase enhanced the HMF yield, as previously reported for other solid acid catalysts. The reaction products were analyzed by HPLC. High glucose conversion is achieved for all the catalysts at 175ºC, but maximum values were obtained with the Zr-HMS catalyst. However, the HMF yield begins to decrease after the maximum value is attained due to side reactions. Despite this fact, high HMF yields were observed in all cases, but it should be noted that the HMF yield with Zr-HMS is higher at shorter reaction times, in comparison with the other catalysts. For this reason, the catalytic performance of Zr-HMS was studied at 150ºC, in such a way that similar values of HMF yield than those obtained at 175ºC can be reached, but at longer reaction time. The optimization of different experimental variables has been performed, and structure-activitystability relationships were proposed after the characterization of fresh and spent catalysts.
Keywords: Biomasa vegetal; Catalizadores; Glucosa; Biomass; Glucose; 5-hydroxymethylfurfural; Mesoporous silica; Dehydration